2008
DOI: 10.1089/met.2008.0007
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Low High-Density Lipoprotein Cholesterol Concentrations and Other Dyslipidemic Phenotypes in an Iranian Population

Abstract: The prevalence of dyslipidemia, especially low HDL cholesterol, in Iranian adults is very high. Urgent preventive programs and changes in lifestyle are needed in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…A high prevalence of low HDL-C has been reported previously in Iranian population [25, 26] and is very close to that was reported from Turkish [27]. This could not only be attributed to environmental factors but may also be due to genetic predispositions.…”
Section: Discussionsupporting
confidence: 86%
“…A high prevalence of low HDL-C has been reported previously in Iranian population [25, 26] and is very close to that was reported from Turkish [27]. This could not only be attributed to environmental factors but may also be due to genetic predispositions.…”
Section: Discussionsupporting
confidence: 86%
“…In a survey comparing bus drivers and professional workers in Taiwan, the prevalence of high cholesterol and triglyceride levels in the drivers and professional workers was reported 34.4%, 69.4%, and 29.9%, 30.6%, respectively[25] which are similar to the results obtained from this study. The prevalence of low HDL levels is 73% and high serum triglycerides 40.6% in Iranian population [28]. In the present study increased total cholesterol (>200 mg/dl) was seen in 35.4% and high triglyceride along with low HDL in 9.9% of the population.…”
Section: Discussionsupporting
confidence: 59%
“…An association between HDL-cholesterol levels and metabolic risk factors such as coronary heart disease were shown (Vega and Grundy, 1996). Study on the components of metabolic syndrome revealed that the most frequent variations of components of metabolic syndrome was HDL-cholesterol (33.3%), which was in agreement with the findings of studies in USA (Heiss et al, 1980), Turkey (Onat et al, 1992), Italy (The Research Group ATS-RF2 of the Italian National Research Council, 1981), Canada (MacLean et al, 1999), UK (Mann et al, 1988) and Iranian population (Sharifi et al, 2008) that the most common found was high prevalence of HDL-cholesterol. According to our results, a component of metabolic syndrome such as HDL cholesterol is one of important risk factors to predict and prevent the early on set of cardiovascular disease and coronary heart disease (MacLean et al, 1999;Isomaa et al, 2001;Meigs et al, 1997;Natali et al, 2006).…”
Section: Discussionsupporting
confidence: 84%